Efeito de diferentes espessuras, técnicas de aplicação e protocolos de resfriamento na resistência à fratura da cerâmica de cobertura aplicada sobre infraestrutura de y-tzp - Lima, Júlia Magalhães da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to evaluate the in vitro influence of cooling protocols and application techniques and the effect of the thickness of veneering ceramics on the fracture resistance of prosthetic crowns. For this purpose, 100 ‘zirconia partially stabilized by yttrium oxide’ frameworks (1 mm thick) were made. Eighty frameworks were divided into 8 groups (n = 10) according to the application technique (stratified or pressed), thickness (1 or 2 mm), and the cooling protocol (slow or fast) of the veneering ceramic. With the remaining 20 frameworks, 20 crowns were prepared by the CAD/CAM/Rapid Layer technique and were divided into 2 groups (n = 10) according to the veneering ceramic thickness (1 or 2 mm); these were also evaluated by Finite Element Analysis. All specimens were mechanically cycled (200 N, 2 x 106 cycles; 3.0 Hz; water at 37 °C). Chipping presence was evaluated by stereomicroscopy after mechanical cycling. All specimens were tested for compressive strength (0.5 mm/minute; 10 kN). We analyzed crowns to determine the possible beginning of the failures. Data, in N, were statistically analyzed with Dunnett’s, t-test, 3-way ANOVA, and Tukey's tests. The fracture load of the CAD/CAM/Rapid Layer crowns was lower, regardless of ceramic thickness, when compared with the other two application techniques tested (p < 0.05). We observed an influence of the cooling protocol (p = 0.0058) and the application technique (p = 0.0001) in the analysis of stratified and pressed techniques. Slow cooling differed from rapid cooling in the pressed ceramic crowns; however, this difference was not observed for the stratified crowns, regardless of the thickness of the veneering ceramic. Failures in the CAD/CAM/Rapid Layer crowns began predominantly at the interface between the resin cement and veneering ceramic, resulting in delaminations of the veneering ceramic, while the other techniques ....

O objetivo desta pesquisa foi avaliar, in vitro, a influência do resfriamento, da técnica de aplicação e do efeito da espessura da cerâmica de cobertura na carga de fratura de coroas totalmente cerâmicas com infraestrutura de zircônia. Foram confeccionadas 100 infraestruturas de zircônia (Y-TZP) com 1,0 mm de espessura. 80 infraestruturas foram divididas em 8 grupos (n = 10) para confecção de 80 coroas de acordo com os fatores “técnica de aplicação” (estratificada e prensada), “espessura” (1 mm e 2 mm) e “protocolo de resfriamento” (lento e rápido) da cerâmica de cobertura. Com as outras 20 infraestruturas foram confeccionadas 20 coroas pela técnica CAD/CAM/Rapid Layer e divididas em 2 grupos (n = 10) de acordo com o fator “espessura da cerâmica de cobertura” (1 mm e 2 mm) e foi realizada Análise de Elementos Finitos. Todos os espécimes foram ciclados mecanicamente (200 N; 2 x 106 ciclos; 3,0 Hz; água/ 37 °C). A presença de chipping foi avaliada através de análise em estereomicroscópio após a ciclagem mecânica. Em seguida, todos os espécimes foram submetidos ao teste de resistência à fratura em compressão axial (0,5 mm/minuto; 10 kN). As coroas foram analisadas para determinar a possível origem da falha. Os dados (N) obtidos foram submetidos à análise estatística, com o Teste de Dunnett, teste t-Student, para a técnica CAD/CAM/Rapid Layer, e ANOVA 3-fatores e teste de Tukey para as demais técnicas. A carga de fratura das coroas confeccionadas pela técnica CAD/CAM/Rapid Layer, independente da espessura, foi menor em relação às outras duas técnicas (p < 0,05), mas houve diferença significativa entre as duas espessuras das coroas confeccionadas por esta técnica. Houve influência dos fatores resfriamento (p = 0,0058) e técnica de aplicação (p = 0,0001) na análise das técnicas estratificada e prensada. O resfriamento lento diferiu....
Keywords: Oxido de zirconio; Cerâmicas odontológicas; Materiais dentários; Resfriamento; Dental materials; Dental ceramics